A Review of Recent Data in the Treatment of Gallbladder Cancer (Bangladesh Journal of Medical Science, 2016)
Gallbladder cancer is now considered a distinct clinical entity, allowing for a separate analysis from that of other malignancies of the biliary tree. Symptoms related to a malignant tumor of the gallbladder include jaundice and abdominal pain, or a palpable abdominal mass that occurs in a late stage of the disease. The majority of patients with operable gallbladder cancer are diagnosed by cholecystectomy performed for presumed benign disease, mostly cholelithiasis, a clinical entity known as incidental gallbladder cancer. Given the poor prognosis if tumor invasion beyond the muscular layer and/or nodal metastasis is found, adjuvant treatments have been implemented, but few data are available to guide treatment decisions in this setting. For advanced disease, a multidisciplinary treatment approach including biliary drainage procedures and palliative support is needed in the management of this aggressive disease. Palliative chemotherapy with a combination of gemcitabine and cisplatin or oxaliplatin is the standard treatment based on the findings of two phase III trials that showed improved overall survival compared to single-agent chemotherapy and best supportive care. Several phase II studies have been reported investigating the role of targeted agents against EGFR, VEGF, HER2, and MEK. International collaboration to enhance our knowledge of gallbladder cancer should be encouraged.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.320-325